Spondyloepimetaphyseal dysplasia with neurodegeneration associated with AIFM1 mutation – a novel phenotype of the mitochondrial disease. Issue 1 (2nd June 2016) - Mierzewska, H.; Rydzanicz, M.; Biegański, T.; Kosinska, J.; Mierzewska‐Schmidt, M.; Ługowska, A.; Pollak, A.; Stawiński, P.; Walczak, A.; Kędra, A.; Obersztyn, E.; Szczepanik, E.; et al.
Abstract : In 1999, based on a single family, spondyloepimetaphyseal dysplasia (SEMD) with mental retardation (MR) was described as a novel syndrome with probably X‐linked recessive inheritance and unknown molecular defect (MIM 300232). Our purpose was to search for the causative defect in the originally described family and in an independently ascertained second family. All patients had slowly progressive neurodegeneration with central and peripheral involvement and identical skeletal dysplasia. Whole exome sequencing performed in two subjects showed a single plausible candidate – the p.Asp237Gly variant in AIFM1 (chr. Xq26.1). The p.Asp237Gly segregated with disease as indicated by linkage analysis [maximum logarithm of odds score (LOD) score at theta 0 for the two families was 3.359]. This variant had not been previously reported and it was predicted to be pathogenic by Polyphen2, SIFT, MutationTaster and Mutation Assessor. AIFM1 encodes mitochondria associated apoptosis‐inducing factor. The AIFM1 gene has been linked with COXPD6 encephalomyopathy (MIM 300816), Cowchock syndrome (MIM 310490) and X‐linked deafness with neuropathy (DFNX5, MIM 300614), none of which are similar to SEMD‐MR. Our results place SEMD as the third instance of a skeletal phenotype associated with a mitochondrial disease (the others being EVEN‐PLUS syndrome caused by mutations of HSPA9 and CODAS syndrome due to LONP1 mutations). Abstract :